Corrosion of Stainless Steels in the Marine Splash Zone - Bailey, Stuart; Li, X. (Trans Tech Publications Inc, 2013)
Splash zone corrosion was investigated for a number of selected corrosion resistant alloys including in synthetic seawater. Stainless steels 304 and 316 and duplex stainless steels 2205 and 2507 were all investigated. A laboratory apparatus designed to simulate the wetting by a splash, and the subsequent drying through exposure to the weather, was used for this study. The corrosion potential showed a distinct evolution throughout the wet – dry cycle, compared to a sample maintained under constant immersion. However, the corrosion potential gave no indication of susceptibility to pitting corrosion. On the other hand, examination under an infinite focus microscope revealed significant pitting in the samples subjected to wet – dry cycling compared to those maintained under constant immersion.